Bester (beluga ♀ × starlet ♂) production and comparing their growth with beluga in Iran - Baradaran Noveiri, Shahrouz; Bahmani, M.; Abdolhay, H.; Hosseini, M.R.; Chakmehduz, F.; Hallajian, A.; Darvishi, S.; Farabi, M.V. (Iranian Fisheries Science Research Institute, 2009)
Aquaculture for human consuming species is being considered as the first substitution of catching aquatic species due to increase of human population and decrease of wild aquatic stocks. In this study, the hybrid sturgeon Bester (female beluga x male sterlet ) was produced for the first time in Iran. Sperm of 1.35 kg male Acipenser ruthenus was used to fertilize the eggs of 125 kg female Huso huso in Shahid Marjani Sturgeon propagation center (Agh Ghala, Golestan province). The fries of bester and control treatment of beluga were transported to International Sturgeon Research Institute (Rasht) after about one month by reaching to 490 mg and 377 mg of weight respectively. All fishes fed by artificial concentrated food (48-50% protein and 15-17% fat) after a period of feeding with Artemia and Daphnia. Sorting was carried out according to increase of fish weight for both fishes. Results showed that the imported sterlet spawners were not at the high maturation stages and especially the males had not suitable sperm quality. It showed that up to 2 months of age , these was no significant difference between bester and beluga weight but from this age up to 2 months of age the weight of beluga was greater. Meanwhile from 2 months old up to the end of the study (21 months) the weight of bester sample was significantly greater than beluga. The comparison of FCR for the whole rearing period showed no difference between bester and beluga (2.4 and 2.3 respectively). In general, the increase and decrease pattern of GR and SGR were coincided to each other, but showed monthly differences. Growth rate (GR) and specific growth rate (SGR) of bester were greater than beluga from 4th and 3rd month of rearing period respectively. Iranian Fisheries Science Research Institute Published